Analysing the possibility to implement Content and Language Integrated Learning (CLIL) in Senior High School in Indonesia - Akhmad Affandi; Auliyanti Sahril Nurfadhillah (Jurusan Teknik Informatika dan Komputer, 2023)
This paper explores the feasibility of implementing the Content and Language Integrated Learning (CLIL) approach in the Indonesian education system, focusing on four key dimensions: the education system, student assessment, teacher readiness, and parental perspectives. The qualitative approarced was used to conduct thematic analysis in the form of desk research and it will be employed to categorize the information into themes, focusing on education system, students, teachers, and parents’ aspects as dimensions of feasibility. The implementation of CLIL approach has already spread over the world in the past two decades which begins with movement of European Commission Policy. The Longitudinal research has been conducted to give a new insight regarding CLIL implementation. However, previous research scope is limited only for higher education. Having discuss four considerations that have to take into account, it can be therefore concluded that CLIL can be implemented in Senior high school level in Indonesia. The most pivotal factor is institutional support from government in which regulation regarding education goal can be arranged. In addition, the availability of prospective teacher is beneficial for sustain implementation, although they need pre-sessional and in-sessional training before teaching process. The other reason is that student would be free of national examination pressure so that they would be able to focus on sharping language skill in gaining communicative competence rather than mastering grammar. Absolutely, this condition provides a promising opportunities to apply CLIL approach and Task- based learning which aims to build communicative competence. However, it is still necessary to carry out longitudinal research in different context and level of students to unveil robustness and drawbacks of this approach.